The Use of Online Quizz During Bipa Learning in New Delhi - Kurniawan Rachman, Muhammad (International Journal of Transdisciplinary Knowledge, 2024)
This study explores the use of online quizzes in Indonesian for Foreign Speakers classes in New Delhi. This study conducted a survey of 28 respondents to find out their opinions about the use of online quizzes, especially Kahoot, Wordwall, and Quizziz. The results showed that 71% of respondents gave a perfect score of 10 out of 10 to the use of online quizzes. The majority of students chose Kahoot as their favorite online quiz platform, while others chose Quizziz and a combination of the three. The study concluded that online quizzes were considered an effective way to evaluate and summarize class material by students.